The effect of aphidicolin on DNA synthesis in isolated HeLa cell nuclei. - Wist, E (1979)
The effect of the inhibitor aphidicolin on DNA synthesis in isolated nuclei from HeLa cells and on the activities of partially purified DNA polymerases has been tested. Aphidicolin inhibited DNA synthesis and DNA polymerase alpha very efficiently whereas DNA polymerases beta and gamma were insensitive to the drug. The results indicate that DNA polymerase alpha is the polymerase active during elongation as well as in the gapfilling process of discontinuous DNA synthesis.